Fault-Tolerant Strategy for More Reliable Cascaded H-Bridge Inverters - Kim, Min Sol; Baek, Ju Yoen; Lee, Kyo Beum; Ko, Youngjong (2024 27th International Conference on Electrical Machines and Systems, ICEMS 2024, 2024)
This paper introduces a fault-tolerant strategy designed for Cascaded H-Bridge multilevel inverters (CHMI), enhancing reliability through a discontinuous modulation method under open-switch failures. The inverter comprises multiple single-phase H-bridge cells, featuring high-quality, low-power-loss semiconductor devices. Despite their advantages, the extensive use of semiconductor devices in CHMI increases the risk of failure. Since these devices are critical fragile components in the power conversion system, their reliability significantly impacts the system's overall reliability. The proposed fault-tolerant method reduces power loss in these devices by employing a discontinuous pulse-width modulation based neutral point shift, compared with the traditional sinusoidal pulse-width modulation. Theoretical loss analysis evaluates the power loss in the semiconductor devices, and simulation results demonstrate the effectiveness of the proposed fault-tolerant strategy.
Keywords: Cascaded H-bridge; Cascaded H-bridge inverters; Discontinuous modulation; Fault-tolerant strategy; Modulation methods; Multi Level Inverter (MLI); Open-switch failure; Powerloss; Single phasis; Switch failure; Cascaded H-bridge inverter; Fault-tolerant strategy; Open-switch failure; Reliability